An exploratory study in the use of direct quotation by L2 entry level Bachelor students. Issue 40 (July 2019) - Docherty, Peter
Abstract: This study examines the use of direct quotation in essays on English literary analysis written by entry level L2 (Czech) Bachelor students. A corpus of 188 student essays was compiled, tagged and interrogated to explore the lexical and typographic form of the direct quotations as well as the students' surrounding co-text. The five areas studied were: frequency, source, typographic accuracy, citation accuracy and method of textual integration including reporting verbs. The results show that L2 Bachelor students with no previous experience with EAP do use direct quotation extensively in their academic writing and most cite their source appropriately at least once per essay. There were however, issues regarding textual integration. As well as the usual integration methods of embedding and introductory constructions, most students use an idiosyncratic and non-standard form of free-standing quotation, and/or 'shoehorned' quotations. Shoehorned direct quotations are defined in this article as typographically embedded quotations that are contextually free-standing. Because these forms of integration lack any original lexis written by the student which cohesively links the quotation to the co-text, coherence and rhetorical function are at risk of being compromised. The use of such methods can be considered part of the L2 EAP writing development stage.